African Americans against the bomb : nuclear weapons, colonialism, and the Black freedom movement - Intondi, Vincent J. (Stanford nuclear age series., 2015)
Well before Rev. Dr. Martin Luther King, Jr. spoke out against nuclear weapons, African Americans were protesting the Bomb. Historians have generally ignored African Americans when studying the anti-nuclear movement, yet they were some of the first citizens to protest Truman's decision to drop atomic bombs in Hiroshima and Nagasaki in 1945. Now for the first time, African Americans Against the Bomb tells the compelling story of those black activists who fought for nuclear disarmament by connecting the nuclear issue with the fight for racial equality. Intondi shows that from early on, blacks in.